2019
DOI: 10.1109/access.2019.2903081
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Artificial Bee Colony Algorithm and BP Neural Network for Software Aging Prediction in IoT Environment

Abstract: Software aging is a common phenomenon that exists in systems that require long periods of operation, especially in Internet-of-Things environments. The back propagation (BP) neural network has been adopted widely to predict the trend of software aging. However, the weight and threshold of the BP neural network are randomly initialized, so it is easy to get the unsatisfactory local optimal solutions and the convergence speed of computing is slow. In this paper, we propose a novel software aging prediction metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Another issue in IoT environments is occurring faults in the result of software aging. Liu and Meng [45] proposed a method to predict software aging. The method works based on a neural network with Back Propagation (BP) error.…”
Section: Related Workmentioning
confidence: 99%
“…Another issue in IoT environments is occurring faults in the result of software aging. Liu and Meng [45] proposed a method to predict software aging. The method works based on a neural network with Back Propagation (BP) error.…”
Section: Related Workmentioning
confidence: 99%
“…They showed that this method increased the prediction precision and recall. In order to forecast performance anomaly in IoT, Liu and Meng et al [24 ] utilised BP neural network union artificial bee colony method to fit Google's data and then judged whether software system was in ageing state. However, this method only considered the non‐linear characteristics of data and ignored the influence of network structure for software ageing prediction.…”
Section: Related Workmentioning
confidence: 99%
“…A great progress in solving complex numerical optimization problems has achieved in [19,20]. With the continuous improvement and optimization, ABC has been applied in more fields, such as workshop scheduling [21][22][23][24][25] software aging prediction [26], machine learning [27], multi-objective optimization [28], dynamic optimization [29,30] and so on.…”
Section: Introductionmentioning
confidence: 99%